Incidence of Carotico-clinoid Foramen and Interclinoid Osseous Bridge in Dry Human Skulls in Sudan_ Neurosurgical Interest - Seddeg, Yasser; Elbadawi, Kamalelden (My University, 2020)
Background: Anterior clinoid process is usually drilled in order to approach cavernous sinus and related structures in neurosurgical operations. The presence of carotico-clinoid foramen and interclinoid osseous bridge create difficulties while approaching anterior clinoid process and increases the risks of injury to the internal carotid artery and nearby structures. Aim: To observe incidence, anatomy of carotico-clinoid foramen and interclinoid osseous bridge in the Sudanese dry skulls. Methods: This was a cross sectional study, conducted in the departments of anatomy in different medical schools in Sudan between the period from June 2019 to January 2020. Total 30 dry adult human skulls were examined to observe incidence of carotico-clinoid foramen and of interclinoid osseous bridge. Result: The incidence of carotico-clinoid foramen was 13.3% (4 skulls out of 30). The foramen was bilaterally present in one skull (n=1/30, 3.3%) and unilateral in 3 skulls (n=3/30, 10%). Type I bridge is the carotico-clinoid foramen itself, the Type II interclinoid osseous bridge was found in one skull (n=1/30, 3.3%) , no Type III and Type IV bridges were observed in the present study. Conclusion: the presence of this foramen and interclinoid osseous bridge can complicate neurosurgical operations in cavernous sinus, sellar and para-sellar regions. Therefore, the detailed anatomical knowledge is very important to decrease complications and to increase success rates of neurosurgical operations in this area.
Keywords: carotico clinoid foramen; clinoid process; clinoidectomy; clinoid drilling